The Role of Nutrition on the Immune Response - Felisha Febriane Balafif; Anggun Rafisa; Faisal Kuswandani; Nuroh Najmi (Sean Institute, 2023)
The immune system reaction against infections and other foreign substances is known as the immune response. Nutrition is a critical component in the modulation of the immune system, hence the importance of a balanced diet. Better nutrition improves health, reinforces the immune system, contributes to longevity, and decreases the chance of non-communicable diseases. Thus, nutrition, health, and immune system are strongly connected. The aim of the present study is to evaluate current knowledge on the role of nutrition on the immune response. The article was conducted of two databases and were limited to the period from January 2018 to April 2023 with a combination of the following keywords: “role